2022
DOI: 10.3390/agronomy12112778
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Knowledge and Acceptance of Microalgae in Almería Greenhouse Horticulture

Abstract: Almería horticulture in SE Spain hosts the largest concentration of greenhouses in the world and faces important environmental sustainability challenges. Microalgae-derived applications are efficient nature-based solutions as they are used for wastewater regeneration or as biostimulants and biopesticides in agriculture. However, farmers’ knowledge and acceptance of microalgae-derived applications remain unknown, which is a major barrier to its commercialization. This study explores current farmers’ knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another survey conducted by Ruiz-Nieto et al [ 127 ] about farmers’ knowledge and acceptance of microalgae in horticulture greenhouses in the city of Almeria revealed that despite the lack of a solid understanding of microalgae beneficial uses in agriculture, farmers conceived microalgae as having potential benefits to agriculture. In light of this result, it is essential to encourage local efforts to promote the use of microalgae in the cropping system, especially in countries where agriculture is an economic pillar.…”
Section: Commercialized Microalgae- and Cyanobacteria-based Biostimul...mentioning
confidence: 99%
“…Another survey conducted by Ruiz-Nieto et al [ 127 ] about farmers’ knowledge and acceptance of microalgae in horticulture greenhouses in the city of Almeria revealed that despite the lack of a solid understanding of microalgae beneficial uses in agriculture, farmers conceived microalgae as having potential benefits to agriculture. In light of this result, it is essential to encourage local efforts to promote the use of microalgae in the cropping system, especially in countries where agriculture is an economic pillar.…”
Section: Commercialized Microalgae- and Cyanobacteria-based Biostimul...mentioning
confidence: 99%